Increasing The Ability To Recognize Number Symbols Through The Activities Of Playing Snakes And Stairs For Children Of Group A In Tk Aisyiyah Busthanul Athfal 6 Candi: Peningkatan Kemampuan Mengenal Lambang Bilangan Melalui Kegiatan Bermain Ular Tangga Pada Anak Kelompok A Di Tk Aisyiyah Busthanul Athfal 6 Candi - Retno Nur Hardani; Luluk Iffatur Rocmah (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the lack of ability of group A children in Kindergarten Aisyiyah Busthanul Athfal 6 Candi in recognizing the symbol of numbers. Based on a preliminary study in Kindergarten Aisyiyah Busthanul Athfal 6 Temple found that 70.59% of 17 Kindergarten A children were still wrong in recognizing good symbols when asked to say by sorting number cards, dancing lines according to the number of drawings, counting many marbles and pasting numbers right. These problems are caused by the introduction of non-matching number symbols, and non-concrete learning media (using worksheets). The solution provided is the introduction of the number symbol by playing snakes and ladders with steps to recognize the symbol number. This research is a classroom action research (CAR) that uses Kemmis and Mc. Taggart. The subject of the action was the children of group A